Nutritional support for preterm infants: a study of current perceptions and practices of parenteral and enteral nutrition and complementary foods - Elfzzani, Zenab (2019)
The incidence of preterm birth is increasing globally. In the UK, approximately 7% of live born infants are born prematurely. Premature birth is one of the most important issues in perinatal medicine, leading to a considerable global burden of diseases due to high mortality and morbidity in these vulnerable infants. Suboptimal nutritional intakes during the early postnatal and post-discharge period, including inappropriate weaning practices contribute to malnutrition, suboptimal growth and poor neurodevelopment outcome among infants born preterm.